Bilateral Ductal Stenting for Discontinuity of the Pulmonary Artery via the Femoral and Carotid Arteries in an Infant - Osman Baspinar; Derya Aydin Sahin (Case Reports in Cardiology)
Bilateral ductal stenting should be performed in cases of discontinuity of the pulmonary branches and pulmonary atresia. Performing this procedure via the carotid artery in small infants can be very difficult and challenging. We present a case of bilateral ductal stenting via both the femoral and carotid arteries in a little child with tetralogy of Fallot with pulmonary atresia and a nonconfluent pulmonary artery and bilateral ductus arteriosus.